2006
DOI: 10.1682/jrrd.2005.06.0102
|View full text |Cite
|
Sign up to set email alerts
|

Retinal locus for scanning text

Abstract: Abstract-A method of mapping the retinal location of text during reading is described in which text position is plotted cumulatively on scanning laser ophthalmoscope retinal images. Retinal locations that contain text most often are the brightest in the cumulative plot, and locations that contain text least often are the darkest. In this way, the retinal area that most often contains text is determined. Text maps were plotted for eight control subjects without vision loss and eight subjects with central scotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…It is still an open question whether patients use a single preferred retinal locus (PRL) or multiple PRLs during a reading task. 89,90 What consequences would the use of multiple PRLs entail regarding our ability to measure fixation clusters? The most extreme consequence would occur if a difficult word was processed by alternating between a left and a right reading PRL.…”
Section: Discussionmentioning
confidence: 99%
“…It is still an open question whether patients use a single preferred retinal locus (PRL) or multiple PRLs during a reading task. 89,90 What consequences would the use of multiple PRLs entail regarding our ability to measure fixation clusters? The most extreme consequence would occur if a difficult word was processed by alternating between a left and a right reading PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Duret, Issenhuth and Safran 17 and Déruaz, Whatham, Mermoud, et al 18 both found subjects who used multiple PRLs to read text and altered the PRL selected dependent on text size in the former study. Timberlake, Sharma, Grose et al 19 reported that some subjects used PRLs for reading that differed from the PRL used to maintain fixation on a small stimulus. Similarly, Crossland, Crabb and Rubin 20 observed age-related macular degeneration subjects that used PRLs that differed between fixation of a point stimulus and fixation of a word.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Moreover, some patients do not use the same PRL in a fixation task and during reading. 22 In addition, some patients may use different PRLs during reading, thus causing some variability in viewing eccentricity, especially with scotomas of nonregular shape. [23][24][25] Consequently, the scotoma area is probably a better predictor of reading eccentricity than PRL distance from the fovea.…”
mentioning
confidence: 99%